Dynamiques de résistance aux normes révolutionnaires à Cuba - Marie-Laure Geoffray (Cahiers des Amériques Latines)
The norms of the revolutionary regime are, in Cuba, inscribed into space. They can be analyzed as performative signs, which at the same time remind of the constant presence of power and categorize people according to their conformity to those norms. But since the economic crisis of the 1990s, some logics at work in the Cuban society question the regime’s capacity to generate a homogeneous revolutionary socialization. There exists striking dynamics in groups of young artists. They try to emancipate from the revolutionary norms and to recall a political, historical and artistic heritage distinct from that which is promoted by the leaders of the country. Their objective is to socialize the capacity for creation in order to promote diversity and the plurality of modes of thought and action.